2019
DOI: 10.1101/709105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

NBR1-mediated p62-liquid droplets enhance the Keap1-Nrf2 system

Abstract: 10 p62/SQSTM1 is a multivalent protein that has an ability to cause a liquid-liquid phase separation and serves as a receptor protein that participates in cargo isolation during selective autophagy. This protein is also involved in the non-canonical activation of the Keap1-Nrf2 system, a major oxidative stress response pathway. Here we show a role of Neighbor of BRCA1 gene 1 (NBR1), an autophagy receptor structurally similar to 15 p62/SQSTM1, in the p62-liquid droplet formation and the Keap1-Nrf2 pathway. The … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(42 citation statements)
references
References 48 publications
2
40
0
Order By: Relevance
“…Intriguingly, it has been shown that upon ubiquitin binding p62 acquires liquid like properties since it forms droplets that serve as interactive nodes in the context of selective autophagy. The droplet formation is favoured by the interaction through the PB1 domain of p62 with NBR1, as previously mentioned [ 31 ]. Beside p62 regulative phosphorylation within the UBA domain, another important post translational modification is represented by acetylation.…”
Section: P62 Structure Post-translational Modifications and Confmentioning
confidence: 53%
See 1 more Smart Citation
“…Intriguingly, it has been shown that upon ubiquitin binding p62 acquires liquid like properties since it forms droplets that serve as interactive nodes in the context of selective autophagy. The droplet formation is favoured by the interaction through the PB1 domain of p62 with NBR1, as previously mentioned [ 31 ]. Beside p62 regulative phosphorylation within the UBA domain, another important post translational modification is represented by acetylation.…”
Section: P62 Structure Post-translational Modifications and Confmentioning
confidence: 53%
“…While the dimeric form of p62 is substantially inactive with respect to autophagy, polymerization of p62 in a filamentous form, which renders the protein functional, is promoted by the interaction of the protein with the autophagic receptor NBR1 (the neighbor of BRCA1 gene). This factor specifically binds to PB1 domain and cooperates with p62 in targeting poly-ubiquitinated proteins to the autophagosome during selective autophagy [ 31 ]. Jacobi at al.…”
Section: P62 Structure Post-translational Modifications and Confmentioning
confidence: 99%
“…The p62 condensates show gel-like behaviors, namely slow fusion and low mobility (Sun et al, 2018;Zaffagnini et al, 2018), which suggests that the gel-like state may ensure efficient autophagic degradation of these condensates. Consistent with the notion that higher liquidity is not favorable for degradation, overexpression of NBR1, which promotes p62-mediated phase separation and also dramatically increases the mobility of p62 in the condensates, impairs autophagic degradation of p62 condensates (Sánchez-Martín et al, 2020;Zaffagnini et al, 2018). Aberrant p62-positive aggregates, such as Mallory-Denk bodies, α1 antitrypsin aggregates, Lewy bodies, and huntingtin aggregates, accumulate in a diversity of diseases (Yamamoto and Simonsen, 2011).…”
Section: Llps Mediates the Assembly Of Aggregates Containing P62 And mentioning
confidence: 61%
“…No difference was noted in the protein levels of TRIM21 (Appendix Fig S4A), which is the E3 ligase that conjugates the K63‐linked ubiquitin chains to p62 (Pan et al , 2016). Recently, K63‐linked poly‐ubiquitin chain and p62‐interacting proteins such as DAXX, NBR1, and TAK1 were shown to facilitate formation of p62 bodies (Sun et al , 2018; Zaffagnini et al , 2018; Kehl et al , 2019; Yang et al , 2019; Sanchez‐Martin et al , 2020). To evaluate whether MOAP‐1 regulates p62 bodies through influencing the interaction of p62 with these proteins, we performed co‐immunoprecipitation (co‐IP) experiments on HepG2 cells stably overexpressing Myc‐MOAP‐1 or Myc‐only control.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, in mice, p62 is required and sufficient to mediate liver tumorigenesis through enhancing the Nrf2 and mTORC1 signaling pathways, separable from its role as an autophagy receptor (Saito et al , 2016; Umemura et al , 2016). p62 activity is known to be regulated by multiple mechanisms that modulate its ability to form aggregates and to recruit Keap1 and ubiquitylated substrates (Matsumoto et al , 2011; Ichimura et al , 2013; Cha‐Molstad et al , 2015; Pan et al , 2016; Lee et al , 2017; Peng et al , 2017; Carroll et al , 2018; Kehl et al , 2019; Xu et al , 2019; Yang et al , 2019; You et al , 2019; Sanchez‐Martin et al , 2020). More recently, p62 was shown to undergo liquid–liquid phase separation and the condensates formed, appearing as “aggregates” or “bodies” visually, are in fact a dynamic structure undergoing fusion constantly (Sun et al , 2018; Zaffagnini et al , 2018; Yang et al , 2019; Sanchez‐Martin et al , 2020).…”
Section: Introductionmentioning
confidence: 99%